Workshop Report: National Crop Insurance Programme: Challenges and Opportinities - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), South Asia together with the International Food Policy Research Institute (IFPRI, New Delhi) organised a one day workshop on 1 April 2014, in New Delhi, titled: ‘National Crop Insurance Program (NCIP): Challenges and Opportunities’. The NCIP is to be implemented during the XII Plan and strives to merge existing agricultural insurance schemes in order to serve farmers better. While it provides several new opportunities and addresses earlier constraints, its operation may pose new challenges to government bodies, farmers and the insurance industry. In order to review various aspects of this programme, and from the perspective of different stakeholders, the workshop brought together state and national-level government officials, researchers, and industry representatives to deliberate and discuss key points and recommend suggestions. In all, 36 participants attended the workshop.